Gestão gerencialista e as implicações para a subjetividade dos auxiliares judiciários do Maranhão - COSTA, Ester Nayara da Silva Moura (2023)
This dissertation presents the results of a research on the psychodynamics of pleasure and suffering in the work of judicial assistants at the Court of Justice in Maranhão state. Through the epistemological bias of the psychodynamics of work founded by Christophe Dejours and also based on historical-dialectical materialism, we established as a general objective the analysis of the work of TJ/MA judicial assistants and the crossing of management tools and as well as the repercussions on health and the subjectivity of these professionals. The specific objectives aimed to investigate the TJ management model and the repercussions on the mental health and subjectivity of judicial assistants; to characterize the activity of the judicial assistant and his relationship with the judicial secretaries; to understand the meanings that judicial assistants attribute to their work; to identify experiences of pleasure and suffering in the work of legal assistants; to analyze the mediation strategies used by judicial assistants in their daily work. The methodology used was a semi-structured interview with 4 judicial assistants and 2 judicial secretaries. We observed that this worker does not escape the flexibilization and precariousness of work. We confirmed that the work dynamics of the legal assistant has several nuances that often open up gaps between the prescribed work and the real one, demanding creativity from this worker. We note that due to the financial stability provided by the condition of public servants in the judiciary, assistants end up submitting themselves to the role below their level of education. Finally, we found that satisfaction is restricted to social recognition by the social community and is partly linked to the results and goals of the institution. The slowness of the judicial system, due to its own procedural rites and to the lack of sufficient servers for the high demand for processes, causes discomfort and displeasure among servers, especially after the implementation of the Electronic Digital Process.